2010
DOI: 10.2328/jnds.32.1
|View full text |Cite
|
Sign up to set email alerts
|

Earthquake Resistance of Adobe Reinforced by Low Cost Traditional Materials

Abstract: Adobe houses are expected to continue providing the housing needs of rural poor people because of their energy effi ciency, comfort, and cost effectiveness. Unfortunately traditional adobe constructions are very poor against earthquakes and cause signifi cant loss of life and property. Seismic defi ciencies of such structures are mainly due to brittleness and low strength of the blocks; low strength as well as poor bonding of mortar; and lack of structural integrity. Considering affordability, availability, en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 7 publications
0
22
0
Order By: Relevance
“…The fibers prevented crack-face separation mainly through a stretching process, which provided an extra energy-absorbing capacity while also reducing the stress around the micro-cracked region surrounding the crack-tip [42]. The observed enhancement in ductility and flexibility of the reinforced blocks as observed in this research improves the capacity of blocks to store elastic energy providing some resistance to out-of-plane loads at the system/wall level [8,16,17].…”
Section: Influence Of Fibers On Block Deformationmentioning
confidence: 84%
See 2 more Smart Citations
“…The fibers prevented crack-face separation mainly through a stretching process, which provided an extra energy-absorbing capacity while also reducing the stress around the micro-cracked region surrounding the crack-tip [42]. The observed enhancement in ductility and flexibility of the reinforced blocks as observed in this research improves the capacity of blocks to store elastic energy providing some resistance to out-of-plane loads at the system/wall level [8,16,17].…”
Section: Influence Of Fibers On Block Deformationmentioning
confidence: 84%
“…Fiber-reinforced blocks can withstand higher stresses by absorbing high amounts of energy making them particularly important in earthquake prone regions [8]. It has been demonstrated that sisal [11,12], coconut fiber [13][14][15], straw [16], polyethylene [10], jute [17,18], are all feasible options for CEB reinforcement. Improvement in ductility is widely accepted as a key benefit of fiber reinforcement in soil-cement composites.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The application of adobe materials faces several constraints due to their brittle behaviour, low tensile strength and deterioration when exposed to moisture. However, the properties of adobe can be improved by mechanical compaction, chemical stabilisation with cement, lime and bitumen, and fiber inclusions such as straw [3,6]. Chemical stabilisation can significantly improve strength and water resistance of adobe.…”
Section: Introductionmentioning
confidence: 99%
“…Adobe construction is a type of earthen construction in which sun dried bricks are laid to form the walls of houses. Since soil is often freely available, this affordable construction is the method of choice for many low-income communities in developing countries [1,2]. For example in Sindh Province of Pakistan about 39% of all housing is adobe houses while the percentage in Peru is 60% and in India about 73% [3,4].…”
Section: Introductionmentioning
confidence: 99%